Time-use and wellbeing in Onesi, Namibia - Musingarabwi, Steffanie (Department of Environmental and Geographical Science, 2017)
Men's and women's time-use in relation to wellbeing is well-investigated and understood within the context of the developed world. There has been limited research into the gendered experiences of time-use and three dimensional (3D) wellbeing in rural communities of sub-Saharan Africa and particularly so in semi-arid areas. As a result, failure to appreciate how time-use and wellbeing are experienced by the rural population in semi-arid areas impedes a full understanding of how rural inhabitants spend their time and how this makes them worse off or better off in different aspects of their wellbeing. This subsequently challenges the appropriateness of efforts to improve the lived experience of rural inhabitants. The study aimed to make a contribution to the knowledge gap on time-use and wellbeing by assessing how time-use relates to the experiences of material, subjective and relational aspects of wellbeing in a semi-arid area. It hypothesised that if men and women who are household-heads spend their time-use differently this has implications on their experiences of material, subjective and relational wellbeing. The study adopted a quantitative approach to primary data collection, analysis and interpretation of results. A questionnaire survey consisting of 93 randomly selected male and female headed households was conducted using stratified sampling techniques. Data was analysed using Microsoft Excel and SPSS software including regression analysis and statistical tests (Mann Witney U test) from which descriptive and statistical results were presented in tables and graphs following regression analysis. The study yielded several findings including the importance of personal care for improved subjective wellbeing despite the trade-off with material wellbeing; the importance of age and social grants for ensuring a better experience of material wellbeing; the importance of social connections particularly for widows and widowers; as well as the significance of time spent on leisure and work-outside for improving relational wellbeing. In addition, women's disproportionally high time spent on domestic work leaves them feeling subjectively worse-off while the persistence of traditional gender role division seems to have a determining effect on the time-use and wellbeing experiences of household-heads in the study area. Overall, the study highlights time-use related opportunities and constraints for improving the wellbeing of rural inhabitants in Onesi, Namibia.